Development of Schlieren Visualization System for Study of Flame Characteristics - Muhammad Rubaie bin Mohammad Tahir, Muhammad Rubaie (Universiti Teknologi Petronas, 2009)
The characteristics of flame propagation are one the factors that contribute to efficiency in combustion. Therefore, study on flame characteristics is very important. Schlieren visual imaging system is one of the methods that can be used to study flame propagation due to its capability to capture clear images of the flame. A commercial Schlieren visual system is very costly and usually it is difficult to find a suitable design for specific use in the industry because of limited production in the market. Therefore, development of a suitable and flexible design that can be used for various settings of experiment would be required. The objective of this project is to develop a Schlieren imaging system that can capture flame images. Flame characteristics in real industry are not clearly understood. Thus, this project enables understanding of flame perturbation effect by using Schlieren technique. This project focuses on several parts of study which are critical research on Schlieren techniques, development on Schlieren design and setting, testing on apparatus after fabrication, analysis the flame perturbation image, recommendation on apparatus improvement and and finally conclusion. The methodology of this project includes; literature review, techniques selection, equipment and material selection, design and fabrication, testing, experiment on the apparatus, analysis, improvement and, experiment on flame perturbation characteristics. This project shows that diameter of the lens is the key to enlarge the area of Schlieren image. Further study and research can be done to understand the effect of each component in Schlieren Visualization System to improve the Schlieren image.